Longevity and fecundity of Colasposoma dauricum Mannerheim (Coleoptera Chrysomelidae: Eumolphinae), a pest of sweet potato in Korea - Alaijos, Oliver R. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2005)
The adult longevity and reproductive biology of Colasposoma dauricum were studied in the laboratory. Results showed no significant difference between male and female mean longevity (22.24 d and 22.50 d, respectively). Mean fecundity was 154.77 and 208.00 at 24 C and 28 C, respectively; mean number of eggs per day per female was 30.08 and 34.79 at 25 C and 28 C, respectively. Mean incubation period was 9.74 d at 25 C and 8.37 d at 28 C; 67.00% and 85.09% of the eggs hatched at 25 C and 28 C, respectively.